Et veritas liberabit vos: o catolicismo entre o modernismo e a tradição (1960-2013) - Dias, Juliano Alves [UNESP] (2013)
When one looks at the history of the Church in its last century, there is a difference in attitude between the period before the Second Vatican Council (1962-1965) and his descendants. The Church apparently had left certain positions, however the post- conciliar popes and church documents of the magisterium does not confirm this view. Recently with the pontificate of Benedict XVI (2005-2013) a series of questions about the Vatican and its intentions gained ground in ecclesial environment. The outcome of ultramontanismo (1800-1960) seems to have taken new shape and some of its elements passed through a rereading. Benedict XVI, from his first speech to the Roman Curia, proposed a vision of historical continuity of this council with the Church's past, denying a possible rupture and reaffirming the conviction to certain aspects of the modern world and to what he called the dictatorship of relativism. To assert such a proposition, his pontificate approached conservative sectors of Catholicism and sought to create an official interpretation of the council that put in line with the two thousand year history of the Church, its purpose seems to be the exclusion of interpretations that have made a revolution council the internal ecclesiastical institution and opened to what previously condemned, Modernism. Given these historical perspectives, we intend to study the sixteen documents of the Second Vatican Council, in its eagerness to compare them with previous positions given by the Magisterium of the Church, particularly with the encyclical Quanta Cura of Pius IX in his Syllabus of Errors (1864) and Pascendi Dominici Gregis (1907) of Pope St. Pius X. The primary intention of this work is to see the possible differences between the Vatican and the pre -conciliar magisterium. Secondly , there is the need to examine the performance of the post- conciliar Popes Paul VI , John Paul II and Benedict XVI , the aspiration to understand the process of...